Development of Pedagogical Activity in East and West - Sattorov Vakhob Nakshbandovich (Central Asian Journal of Theoretical and Applied Science, 2022)
The problem of the person, the person, the learner (student), education, the profession (teacher-teacher) has been in the center of attention of advanced religious and secular scholars in all periods of human history and is therefore widely covered in the content of their works. This article discusses the development of pedagogical activity in the east and west.